Spraying against insect injury a prominent factor in orchard management - Houser, John Samuel (My University, 1904)
Introduction: Plants like animals seem to be more subject to disease and parasitic attack when they appear in large numbers than when found singly, and these attacks seem to increase in proportion to the increase in numbers of the plant grown. For many hundreds of years they were considered to be inevitable that they were uncontrollable as far as the hand of man was concerned. But within the last half century, beginning about the time when Paris green was found to successfully combat the Colorado potato beetle (Doryphora decemlineata Say) in America, and a few years later when a mixture of copper sulfate, milk and water was accidentally found in France to prevent downy mildew on the grape, (Peronspora viticola B.& C.), men began to believe that it might be possible, at least in a measure, to control them. Having come to this supposition they at once began experimenting that they might determine with some degree of definiteness to what extent their theory would hold good. As a result of this movement, they not only arrived at the positive conclusion that many of our most injurious insect and plant diseases may be controlled if properly treated, but also many different spraying mixtures were discovered.
Citation: Houser, John Samuel. Spraying against insect injury a prominent factor in orchard management. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Agricultural Management; Pesticides; Insects; Theses